Pediatric Blastic Plasmacytoid Dendritic Cell Neoplasm: A Case Report - Jasper X Zheng; Elham Vali Betts; Denis M Dwyre; Jong H Chung; Ananya Datta Mitra (Clinical Pathology)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive neoplastic process of precursor plasmacytoid dendritic cells. The diagnostic evaluation of this heterogenous entity is challenging, requiring a comprehensive approach of incorporating clinical, morphologic, immunohistochemical, and molecular/cytogenetic evaluations. Optimal management of BPDCN remains controversial, and clinical outcomes continues to be poor. Pediatric cases of BPDCN are rare and to our knowledge, this is the second case of BPDCN described in a Hispanic child, first one was described outside the US in Peru. Here, we report a case of a juvenile patient of Hispanic origin presenting with cutaneous and bone marrow involvement and initially misdiagnosed as a cutaneous infection that resulted in subsequent delaying of necessary chemotherapy for 2 months. Biopsy of the lesion showed diffuse infiltration of immature cells involving the dermis with classical sparring of epidermis. A huge panel of immunohistochemical stains were performed to reach the diagnosis of BPDCN. Staging bone marrow biopsy also revealed involvement by BPDCN. Treatment was not only delayed in this patient but also due to the rarity of BPDCN in pediatric population, the subsequent therapeutic decisions were challenging for the primary oncology team as it was based solely on published literature on adult population. Our case report will not only add one more case in the pediatric age group, but also will also emphasize that although BPDCN has a grave prognosis in the elderly, timely diagnosis with prompt treatment is the key to complete remission in pediatric BPDCN population.